Dvandva and Appositional Compounds in the Food Menu on the Starbucks Cafe Website - Trializa, R; Yuwita, M R (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The objective of this research is to analyze the differences between two types of compounds contained in food names. The discussion includes the basic constituent used to form new words. The data in this study is taken from foods name on the Starbucks Cafe menu, while the object is about the dvandva compound and appositional compounds. This research uses the qualitative method, which is a descriptive method, and the data found is reported in words. The study uses Bauer’s (2001) theory as a reference to explain dvandva (copulative) and appositional compounds. There are 9 data that the writer found on the Starbucks Cafe website. The result shows that there are 4 data of the dvandva compound, and 5 data of the appositional compound. Dvandva and appositional are frequently difficult to distinguish, therefore, the impact of this research is to help distinguish between the two types of compounds and to show the word formation process for the names of a product.